ANALISIS PENGARUH KEBERADAAN LEMBAGA KEUANGAN MIKRO TERHADAP KEMISKINAN DI INDONESIA - Palloan, Ricek; Nafurbenan, Klara Ayu; Saraswati, Birgitta Dian (ANALISIS, 2023)
Poverty is still a problem in every country, especially developing countries like Indonesia. In order to improve the welfare of the Indonesian people, the government seeks to reduce the poverty rate in Indonesia in various ways, one of which is by providing microfinance services. Microfinance institutions are expected to be able to help the poor so that they can obtain capital. The purpose of this research is to analyze the influence of the number of microfinance institutions, the number of loans to microfinance institutions, the assets of microfinance institutions and poverty alleviation in Indonesia. This study uses a quantitative method with panel data regression analysis techniques. The results show that the number of microfinance institutions does not affect poverty in Indonesia, this occurs because the existence of the number of microfinance institutions is not evenly distributed in Indonesia. Then the number of loans disbursed by microfinance institutions has a positive effect on poverty, if the number of loans increases, poverty also increases. return the loan. Financial institution assets have a negative effect on poverty, if assets increase, the poverty rate decreases. Unemployment has a positive effect on poverty, occurs because the level of welfare decreases due to unemployment.